Growth performance and health of lactating lambs consuming milk replacers with different proportions of lactose - Vedovatto, Marcelo; Farinatti, Luis Henrique Ebling; Todero, Cristiano (Revista de Ciências Agroveterinárias, 2019)
The objective was to evaluate growth performance, feed intake and health by suckling Lacaune lambs consuming ewe’s milk or milk replacers with different lactose (LAC) ratios. Thirty-six male lambs with approximately six days of age (4,98 ± 1,20 kg) were used, and evaluated until weaning (60 days of age). These were divided in 12 cohorts, with three animals each, and housed in pens, corresponding to four pens per treatment. The experimental treatments were: Ewe’s milk; Milk replacer 36% LAC, milk replacer containing 36% of lactose and; Milk replacer 29% LAC, milk replacer containing 29% of lactose. The lambs fed with Milk replacer 29% LAC showed lower (p≤0.05) final body weight, average daily gain, total feed intake and worse feed conversion, in relation to the animals treated with Ewe’s milk. The lambs that received Milk replacer 36% LAC did not differ (p>0.05) from the animals treated with Ewe’s milk and Milk replacer 29% LAC for the variables mentioned above. There was no treatment effect (p>0.05) on the mortality or diarrhea rate. Thus, Milk replacer 36% LAC can replace the Ewe’s milk without impairing growth performance, intake and health of lambs, but the use of the Milk replacer 29% LAC, despite not having affected the health, can reduce the growth performance and feed intake in lambs.